Municipal Waste Management in Poland Compared to Other European Union Countries - Agnieszka Poniatowska; Monika Kisiel; Damian Panasiuk (Studia Ecologiae et Bioethicae)
The paper discusses the current state of municipal waste management in Poland compared to other European Union countries. It indicates the amounts of municipal waste generated over the last few years in Poland and other EU countries. The paper compares waste treatment methods in Poland and Europe, such as recycling, composting, thermal treatment and waste disposal. An analysis of municipal waste processing installations in Poland is presented. The trends in the municipal waste management system in recent years have also been described. In the field of municipal waste management in Poland, there have been significant changes. The amount of waste sent to landfills has decreased, and the amount of waste recovered and recycled has increased. These changes are positive and reflect the development of municipal waste management systems in other EU countries. The article indicates the problems and directions of changes in the field of municipal waste management in Poland in the coming years, especially in the context of the implementation of circular economy assumptions and the goals set by the European Union in terms of increase the level of waste recycling and reducing their disposal.